The gut microbiome differs between hygiene-performing and non-hygiene-performing worker honey bees - Y. H. Tola; K. Wagoner; M. K. Strand; O. Rueppell; D. R. Tarpy (Insectes Sociaux, 2025)
Gut microbiomes play a significant role in the health, development, and behavior of numerous species, including honey bees ( Apis mellifera ). Worker honey bees exhibit varying degrees of hygienic behavior, which involves the removal of unhealthy brood to mitigate disease within their colony. However, the potential relationship between hygienic behavior and the honey bee gut microbiome has not been previously investigated. In this study, we compared gut microbiota in honey bees engaged in hygienic behavior (hygiene performers) versus those not exhibiting this behavior (non-hygiene performers) using 16S rRNA gene amplicon sequencing. Proteobacteria, Firmicutes, and Actinobacteria were identified as the predominant phyla. Notably, three bacterial species ( Apilactobacillus kunkeei , Bartonella apis, and Frischella perrara ) were found to be more abundant in hygiene performer bees compared to non-hygiene performer bees. Additionally, hygiene performer bees showed a higher diversity of amplicon sequence variants, with Apibacter mensalis being exclusively present in hygiene performer bees and absent in non-hygiene performer bees. These findings reveal an association between gut microbiota composition and hygienic behavior in honey bees, which may provide a foundation for future research exploring probiotic development and other strategies to enhance honey bee health.

Multiple cryptic lineages and restricted gene flow in the decorator worm Diopatra Cuprea - Adam J. Ziegler; Tina M. Bell; Sarah K. Berke; Allan E. Strand; Erik E. Sotka (Marine Biology, 2025)
The decorator worm Diopatra cuprea Bosc, 1802 (Annelid; Polycheate; Onuphidae) is an ecosystem engineer within high-salinity estuaries of the southern and eastern United States. A previous study revealed five morphologically cryptic mitochondrial lineages across its broad geographic distribution. Here, we explore mitonuclear concordance of these lineages using single nucleotide polymorphisms (SNPs) genotyped with RADseq. We genotyped 3,162 SNPs from 233 D. cuprea and detected four deep lineages in the nuclear genome: a northern US clade (Massachusetts), a single nuclear clade within mid-Atlantic populations (i.e., Virginia south through northeastern Florida), a southeastern Florida clade, and a Gulf of Mexico clade. There was mitonuclear concordance within most individuals for three lineages, while two mitochondrial lineages were detected in a single mid-Atlantic nuclear lineage. Thus, there appear to be four cryptic lineages of D. cuprea that suggest four distinct species that rarely hybridize. Within the mid-Atlantic lineage, we detected increasing genetic isolation of populations with increasing geographic distance, a pattern consistent with low dispersal of D. cuprea larvae. Cryptic diversity within the D. cuprea complex is consistent with other common and geographically widespread annelid and Diopatra species that are now being revealed using high-throughput sequencing.

Physiological trade-offs in male social insects: Interactions among infection, immunity, fertility, size, and age in honey bee drones - Bradley N. Metz; Tatiana Molina-Marciales; Micheline K. Strand; Olav Rueppell; David R. Tarpy; Esmaeil Amiri (Journal of Insect Physiology, 2024)

Perinatal exposure to environmental chemicals that disrupt thyroid function can perturb testis development - Monica K. Draskau; Ida W. Strand; Raul Ayala Davila; Anne-Sofie R. Ballegaard; Mikael Pedersen; Louise Ramhøj; Sofie Rising; Kieu-mi Tran; Marta Axelstad; Josephine Bowles; Anna K. Rosenmai; Cassy M. Spiller; et al. (Environmental Pollution, 2024)

Arthropod diversity in constructed wetlands is affected strongly by shoreline properties but only weakly by grazing - David Åhlén; Jerker Jarsjö; Mats Jonsell; Björn K. Klatt; Lea D. Schneider; John Strand; Peter A. Hambäck (Journal of Biogeography, 2024)
Aim Aquatic‐terrestrial transition zones contain features essential for many species that often benefit wetland biodiversity. Shallow flood‐zone areas and reed beds are indicative of natural wetland habitats; however, how such features affect the native arthropod biodiversity in constructed wetlands is scarcely investigated. We asked how these shoreline features, as well as wetland shoreline properties and grazing management, influence riparian arthropod diversities and habitat specializations. Location Constructed wetlands, Sweden. Taxa Araneae, Coleoptera, Diptera. Methods Taxonomic‐, phylogenetic‐ and trait diversities, along with habitat specialist species richness, were measured in riparian spiders, beetles and selected Diptera in 68 constructed wetlands in two regions of Sweden. We ran structural equation models to estimate direct and indirect effects from shoreline slope, flooded grassland, reed areas and grazing management on group diversities, and used multivariate models to determine drivers on habitat specialist species richness. Results Flooded grassland and reed area, along with shoreline slope influenced arthropod diversities, and responses differed between arthropod groups and diversity metrics. Spider trait diversity was greater in wetlands with larger flooded grassland areas, whilst beetle trait diversity was reduced. Spider phylogenetic diversity was greater in wetlands containing larger reed areas and in wetlands with steeper shorelines. However, species richness in predatory flies was greater in wetlands with more gentle shorelines. Grazing management had limited effects on arthropod diversities; however, species richness in wetland specialist and generalist predatory dipterans was greater in the absence of grazers in wetlands with greater flooded grassland areas. Main Conclusions As requirements vary considerably among arthropods, care must be taken when constructing and managing wetlands to benefit arthropod biodiversity. The present results suggest wetlands with a varied shoreline, albeit with greater proportions of flood areas, or multiple adjacent wetlands with varying shores in a wet landscape and a mild grazing regiment, would accommodate a more diverse arthropod fauna.

Successful large-scale and long-term kelp forest restoration by culling sea urchins with quicklime and supported by crab predation - Hartvig Christie; Frithjof E Moy; Camilla W Fagerli; Eli Rinde; Mette Strand; Lise A Tveiten; Hans K Strand (Marine Biology, 2024)
In 2013, a large scale (70 hectare) kelp forest restoration experiment was conducted in a sea urchin barren that had been stable for 45 years. We used 200 tons of quicklime to eradicate the sea urchin population. Kelp recovered within a year in the lime-treated sites. Quickliming did not significantly affect the abundance of non-target species. Mobile kelp fauna colonized the restored kelps, but at a slower rate than kelp and other macroalgae, probably due to slower dispersal abilities. The monitoring period (2012–2021) encompassed the expansion of invasive red king crabs, which emerged as a novel predator of sea urchins. This led to a gradual decline in sea urchin populations and facilitated kelp recovery also in the control sites. This delayed recovery does not invalid the conclusions of the short-term efficiency of the quicklime treatment, but it makes it difficult to conclude about the long-term effects. The study shows that quickliming can initiate kelp recovery within large urchin barrens. We postulate that the recovery of kelps outside the limed areas was due to crab predation, and that successful kelp restoration in areas with recruitment of sea urchins depends on a persistent top-down control of the urchins.

Spousal bereavement and its effects on later life physical and cognitive capability: the Tromsø study - Bjørn Heine Strand; Asta K. Håberg; Harpa Sif Eyjólfsdóttir; Almar Kok; Vegard Skirbekk; Oliver Huxhold; Gøril Kvamme Løset; Carin Lennartsson; Henrik Schirmer; Katharina Herlofson; Marijke Veenstra (GeroScience, 2024)
Spousal bereavement is associated with health declines and increased mortality risk, but its specific impact on physical and cognitive capabilities is less studied. A historical cohort study design was applied including married Tromsø study participants ( N =5739) aged 50–70 years with baseline self-reported overall health and health-related factors and measured capability (grip strength, finger tapping, digit symbol coding, and short-term recall) at follow-up. Participants had data from Tromsø4 (1994–1995) and Tromsø5 (2001), or Tromsø6 (2007–2008) and Tromsø7 (2015–2016). Propensity score matching, adjusted for baseline confounders (and baseline capability in a subset), was used to investigate whether spousal bereavement was associated with poorer subsequent capability. Spousal bereavement occurred for 6.2% on average 3.7 years (SD 2.0) before the capability assessment. There were no significant bereavement effects on subsequent grip strength, immediate recall, or finger-tapping speed. Without adjustment for baseline digit symbol coding test performance, there was a negative significant effect on the digit symbol coding test (ATT −1.33; 95% confidence interval −2.57, −0.10), but when baseline digit symbol coding test performance was taken into account in a smaller subsample, using the same set of matching confounders, there was no longer any association (in the subsample ATT changed from −1.29 (95% CI −3.38, 0.80) to −0.04 (95% CI −1.83, 1.75). The results in our study suggest that spousal bereavement does not have long-term effects on the intrinsic capacity components physical or cognition capability to a notable degree.

Wild Mountain reindeer Rangifer tarandus tarandus winter foraging: snow-free areas a key resource for feeding - Marijanne Holtan; Olav Strand; Leif Kastdalen; Dag K. Bjerketvedt; Arvid Odland; Roland Pape; Jan Heggenes (Polar Biology, 2023)
In a landscape with patchily distributed forage resources, an animal’s distribution may reflect the distribution of the resources if the population is forage-limited in time or space. This may be particularly explicit in climatically extreme and seasonally variable environments, notably alpine and polar environments during winter. Sustainable management considers the amount of available alpine ground lichen in winter as a predictor of carrying capacity for the last remaining populations of wild European Mountain reindeer Rangifer tarandus tarandus in alpine environments in South Norway. Ground lichen growth is constrained to elevated, wind-blown, snow-free ridges. However, wild Mountain reindeer also persist in areas providing little lichen resources. Our alternative functional hypothesis is that the critical resource is the amount of snow-free feeding areas during winter, which provide direct access to forage, likely to be energy-profitable regardless of the type of vegetation. We sampled animal-borne videos from wild Mountain reindeer during maximum accumulation of snow in late winter/spring, in three contrasting areas providing variable amounts of ground lichen and alternative vegetation resources. Direct observations of reindeer foraging via videos document an active selection and strong preference for feeding on snow-free patches, regardless of type of vegetation. Active ‘cratering’ in snow was not observed. In contrast, walking behaviours occurred much more frequently across snow-covered areas. Remote sensing data and analyses corroborated these observations. In the sustainable management of wild Mountain reindeer amounts of vegetated snow-free areas is an important functional predictor of winter carrying capacity.

Comparative Description and Analysis of Oyster Aquaculture in Selected Atlantic Regions: Production, Market Dynamics, and Consumption Patterns - Johannes A. Iitembu; Daniel Fitzgerald; Themistoklis Altintzoglou; Pierre Boudry; Peter Britz; Carrie J. Byron; Daniel Delago; Sophie Girard; Colin Hannon; Marcia Kafensztok; Francisco Lagreze; Jefferson Francisco Alves Legat; et al. (Fishes, 2023)
In the face of an increasing world population and a subsequent need for an increase in sustainable and healthy food production, low trophic species, such as oysters, emerge as a promising alternative. However, regional variations in oyster production techniques, market dynamics, and consumption patterns create challenges for both the global and local industry’s growth. In this study, a descriptive qualitative analysis of oyster markets across seven Atlantic regions was carried out. The Pacific oyster (Crassostrea gigas) was found to be farmed in most Atlantic regions except the US but is classified as invasive in Sweden and potentially invasive in South Africa. Other farmed and/or harvested species include native species (C. gasar and C. rhizophorae) in Brazil, the American cupped oyster (C. virginica) in the US, and the European flat oyster (Ostrea edulis) in France, Sweden, and the US. In Irish farms, Pacific oysters are primarily for export to European markets. The marine aquaculture sectors of Sweden, South Africa, and Namibia, as well as Brazil’s farming for C. gasar, were found to be underdeveloped. This study also observed a variation in licensing, property rights, and regulatory frameworks. Financial challenges for small businesses, ecological implications of seed production techniques, biosecurity risks, and public health considerations are emphasized as critical areas for attention. This study offers valuable insights into the selected markets and can serve as a useful resource for policymakers, aquaculture practitioners, and stakeholders in optimizing global shellfish industry strategies.

Two invasive Hieracium species’ potential distributions within the Greater Yellowstone Ecosystem were defined using invasion susceptibility models and habitat typing - Christie H. Guetling; Lisa C. Jones; Eva K. Strand; Don W. Morishita; Julia Piaskowski; Timothy S. Prather (Biological Invasions, 2023)
Invasive Hieracium plant species are invading the Greater Yellowstone Ecosystem. The potential distribution of orange hawkweed ( Hieracium aurantiacum) and meadow hawkweed ( Hieracium caespitosum) were estimated using habitat susceptibility models to assist land managers’ management of these invasive plants. The objectives of this study were to: (1) develop models describing susceptibility of ecosystems to hawkweed invasion, (2) identify indicator species of orange hawkweed and meadow hawkweed, (3) determine habitat types where these invasive hawkweeds might occur, and (4) create habitat susceptibility maps for management planning and ground surveys. Models were developed using a Mahalanobis distance similarity technique from remotely sensed biotic and abiotic variables, as well as known location data for orange and meadow hawkweed. Ground validation was conducted to assess model weaknesses and subsequent model modification. Indicator plant species were identified as surrogates to determine the likelihood of hawkweed presence during ground survey. Transect data collected from areas susceptible to invasion also were used to determine habitat types where hawkweed might occur. The best model included eight variables: north–south aspect, east–west aspect, slope, NDVI, NDWI, blue spectral band, green spectral band, and precipitation. High susceptibility (65 + % likelihood of suitable habitat) consisted of 66,000 ha for meadow hawkweed and 35,000 ha for orange hawkweed, 5.0% and 2.7% of the study area, respectively. Meadow hawkweed and orange hawkweed had seven and three indicator plant species, respectively. Predicted hawkweed habitat susceptibility encompassed nine habitat types, ranging from xeric sagebrush steppe to wet forests and they overlapped except at the xeric habitat type. Habitat susceptibility models save costs and allow survey prioritization to those areas most susceptible to invasion.

Ice-confined construction of a large basaltic volcano—Austurfjöll massif, Askja, Iceland - A. H. Graettinger; D. W. McGarvie; I. P. Skilling; A. H. Höskuldsson; K. Strand (Bulletin of Volcanology, 2019)

Lessons from the First Generation of Marine Ecological Forecast Products - Mark R. Payne; Alistair J. Hobday; Brian R. MacKenzie; Desiree Tommasi; Danielle P. Dempsey; Sascha M. M. Fässler; Alan C. Haynie; Rubao Ji; Gang Liu; Patrick D. Lynch; Daniela Matei; Anna K. Miesner; et al. (Frontiers in Marine Science, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Duff Distribution Influences Fire Severity and Post-Fire Vegetation Recovery in Sagebrush Steppe - Nathan I. Weiner; Eva K. Strand; Stephen C. Bunting; Alistair M. S. Smith (Ecosystems, 2016)

Genetic structure along the strandline: Unravelling invasion history in a one‐dimensional system - Sara Ohadi; Peter K. Ades; Rebecca Ford; Allan E. Strand; Josquin Tibbits; Mohsen B. Mesgaran; Roger D. Cousens (Journal of Biogeography, 2016)
Aim To unravel the genetic processes involved in a case of invasion by one species, the self‐incompatible Cakile maritima Scop. (Brassicaceae) in Australia, as it has replaced a related prior invader, Cakile edentula (Bigelow) Hook. Location Southern and eastern coastlines of Australia. Methods Genetic diversity within and between populations was characterized at a continental scale using microsatellite ( SSR ) markers to examine nuclear diversity and cleaved amplified polymorphic sequence ( CAPS ) markers to examine chloroplasts. DNA was sourced from 24 populations of C. maritima along its putative invasion trajectory and, for comparison, from four populations of C. edentula that are currently being invaded by C. maritima . Analysis of Molecular Variance and a Bayesian assignment method were used to explore the data. Results No evidence was found for progressive loss of diversity in C. maritima in the putative direction of range expansion. Western and south‐eastern populations of C. maritima have almost certainly resulted from independent introductions, although there is evidence of very limited gene flow from west to east. There was considerably greater, spatially structured variation in the south‐east, suggesting multiple introductions of C. maritima to that region. We found evidence of hybridization and introgression from C. edentula into C. maritima , both in the two regions where they are currently sympatric and elsewhere. Main conclusions The invasion history of a species spreading in a largely one‐dimensional habitat can still be highly complex and difficult to interpret. Regional patterns of variation in C. maritima indicate several introductions from different parts of the native range, limited gene flow from the first introduction eastwards and genetic drift within Western Australia. There has also been bi‐directional gene flow between this species and C. edentula . The significance of the introgression from C. edentula into C. maritima with respect to natural selection, however, remains to be determined.

Long-term monitoring of western aspen—lessons learned - E. K. Strand; S. C. Bunting; L. A. Starcevich; M. T. Nahorniak; G. Dicus; L. K. Garrett (Environmental Monitoring and Assessment, 2015)

Niche divergence of Abies grandis–Abies concolor hybrids - Todd M. Ott; Eva K. Strand; Cort L. Anderson (Plant Ecology, 2015)

Development of Tools for Integrated Monitoring and Assessment of Hazardous Substances and Their Biological Effects in the Baltic Sea - Kari K. Lehtonen; Brita Sundelin; Thomas Lang; Jakob Strand (Ambio, 2014)

Impact of early salmon louse, L epeophtheirus salmonis , infestation and differences in survival and marine growth of sea‐ranched A tlantic salmon, S almo salar L., smolts 1997–2009 - O T Skilbrei; B Finstad; K Urdal; G Bakke; F Kroglund; R Strand (Journal of Fish Diseases, 2013)
The impact of salmon lice on the survival of migrating A tlantic salmon smolts was studied by comparing the adult returns of sea‐ranched smolts treated for sea lice using emamectin benzoate or substance EX with untreated control groups in the R iver D ale in western N orway. A total of 143 500 smolts were released in 35 release groups in freshwater from 1997 to 2009 and in the fjord system from 2007 to 2009. The adult recaptures declined gradually with release year and reached minimum levels in 2007. This development corresponded with poor marine growth and increased age at maturity of ranched salmon and in three monitored salmon populations and indicated unfavourable conditions in the N orwegian S ea. The recapture rate of treated smolts was significantly higher than the controls in three of the releases performed: the only release in 1997, one of three in 2002 and the only group released in sea water in 2007. The effect of treating the smolts against salmon lice was smaller than the variability in return rates between release groups, and much smaller that variability between release years, but its overall contribution was still significant ( P 0.05) and equivalent to an odds ratio of the probability of being recaptured of 1.17 in favour of the treated smolts. Control fish also tended to be smaller as grilse ( P = 0.057), possibly due to a sublethal effect of salmon lice.

Mammalian cytochrome CYP2E1 triggered differential gene regulation in response to trichloroethylene (TCE) in a transgenic poplar - Jun Won Kang; Hui-Wen Wilkerson; Federico M. Farin; Theo K. Bammler; Richard P. Beyer; Stuart E. Strand; Sharon L. Doty (Functional & Integrative Genomics, 2010)

Spatial patterns on the sagebrush steppe/Western juniper ecotone - Eva K. Strand; Andrew P. Robinson; Stephen C. Bunting (Plant Ecology, 2007)

Population structure in a critically endangered arctic fox population: does genetics matter? - L. DALÉN; K. KVALØY; J. D. C. LINNELL; B. ELMHAGEN; O. STRAND; M. TANNERFELDT; H. HENTTONEN; E. FUGLEI; A. LANDA; A. ANGERBJÖRN (Molecular Ecology, 2006)
The arctic fox ( Alopex lagopus ) in Scandinavia is classified as critically endangered after having gone through a severe decline in population size in the beginning of the 20th century, from which it has failed to recover despite more than 65 years of protection. Arctic foxes have a high dispersal rate and often disperse over long distances, suggesting that there was probably little population differentiation within Scandinavia prior to the bottleneck. It is, however, possible that the recent decline in population size has led to a decrease in dispersal and an increase in population fragmentation. To examine this, we used 10 microsatellite loci to analyse genetic variation in 150 arctic foxes from Scandinavia and Russia. The results showed that the arctic fox in Scandinavia presently is subdivided into four populations, and that the Kola Peninsula and northwest Russia together form a large fifth population. Current dispersal between the populations seemed to be very low, but genetic variation within them was relatively high. This and the relative F ST values among the populations are consistent with a model of recent fragmentation within Scandinavia. Since the amount of genetic variation is high within the populations, but the populations are small and isolated, demographic stochasticity seems to pose a higher threat to the populations’ persistence than inbreeding depression and low genetic variation.

Adaptive Patch Searching Strategies in Fragmented Landscapes - Simone K. Heinz; Espen Strand (Evolutionary Ecology, 2006)

Adolescent smoking and trends in lung cancer incidence among young adults in Norway 1954–1998 - Trond-Eirik Strand; Columbo Malayeri; Petri K.J. Eskonsipo; Tom K. Grimsrud; Jarle Norstein; Tom Grotmol (Cancer Causes & Control, 2004)

Soil carbon stores in Nordic well‐drained forest soils—relationships with climate and texture class - I. CALLESEN; J. LISKI; K. RAULUND‐RASMUSSEN; M. T. OLSSON; L. TAU‐STRAND; L. VESTERDAL; C. J. WESTMAN (Global Change Biology, 2003)
Soil organic carbon (SOC) pools in forest floors and mineral soil to a depth of 100 cm were determined in 234 well‐drained Nordic forest soils from latitude 55–68???°‐N, and longitude 6–28???°‐E. The data were compiled in a database of Nordic forest soils, from literature, and sources of validated data the authors had access to. The SOC pool increased with both mean annual temperature (MAT) and mean annual precipitation (MAP), and the increase with MAT was more pronounced for coarse‐textured soils than for medium‐textured soils. Soil organic carbon in fine‐textured soils was not correlated with MAT and MAP. Differences between texture classes were mainly due to different carbon stores in the upper 40 cm of the mineral soil and in the forest floor. The emphasis on well‐drained soils eliminated the impact of hampered decomposition in hydromorphic soils. Large carbon accumulation in such soils probably explains the negative relationship between SOC and temperature reported in other studies. The increase in SOC with temperature and precipitation is interpreted as an indirect effect of higher net primary production.

Examples of high-frequency EPR studies in bioinorganic chemistry - K. Kristoffer Andersson; Peter P. Schmidt; Bettina Katterle; Kari R. Strand; Amy E. Palmer; Sang-Kyu Lee; Edward I. Solomon; Astrid Gräslund; Anne-Laure Barra (JBIC Journal of Biological Inorganic Chemistry, 2003)

Growth and the effect of grading, of turbot in a shallow raceway system - Hans K. Strand; Victor Oiestad (Aquaculture International, 1997)